The protection of Salicornia rubra from ultraviolet radiation by betacyanins and phenolic compounds - Katherine Jensen (Wiley, 2021)
Abstract Salicornia rubra is a commonly occurring annual species of the salt playas of the Great Basin Desert of the western United States. In such habitats, plants experience high levels of ultraviolet radiation, which could potentially damage DNA. As a member of the Amaranthaceae (Caryophyllales), S. rubra shoots typically contain high concentrations of the red‐violet pigments called betacyanins, which are ultraviolet‐absorbing compounds. Nevertheless, some specimens of S. rubra are green even when growing with full exposure to the sun. We, therefore, tested several hypotheses regarding the causes of variation among S. rubra plants in betacyanin concentration and the role of betacyanins in the absorption of ultraviolet radiation. We measured ultraviolet radiation absorption and the concentrations of betacyanins and phenolic compounds of the cell sap expressed from red and green plants growing in full sun, as well as plants grown under various levels of shade. We found that while betacyanin concentrations were predictable from plant color (red plants contained more betacyanins than green plants), the ability to absorb ultraviolet radiation was determined primarily by the concentration of phenolic compounds, which was determined by the level of exposure to the sun. Therefore, the DNA of green plants growing in full sun appears to be at no greater risk than the DNA of red plants.